(untitled) (Eurasian Research Bulletin, 2024)
The article discusses the issues of enlightenment and the upbringing of a mature generation in the activities of modernists. Enlightenment and generation upbringing are considered very important topics for the activities of modernists nowadays. The main principles of modernist upbringing, various enlightenment models, the specialization of the generation, and its significance are widely demonstrated in this topic. When the content and substance of the subject are considered, the issues of enlightenment and generation upbringing in modernist activities are analyzed extensively and deeply.